أثر برنامج الكتروني قائم على النمذجة والمحاكاة في تنمية مهارات ما وراء المعرفة لدى طلبة الجامعة - مسلم، محسن طاهر Muslem, Mohsen Taher; رديق، مصطفى جواد (المؤسسة العربية للتربية والعلوم والآداب, 2019)
يهدف البحث الحالي إلى تعرف اثر برنامج إلكتروني قائم على النمذجة والمحاكاة في تنمية مهارات ما وراء المعرفة لدى طلبة قسم الفيزياء - كلية التربية – جامعة القادسية . ولتحقيق هدف البحث تمت صياغة الفرضية الصفرية الآتية :- لا توجد فروق ذات دلالة إحصائية عند مستوى دلالة (0.05) بين متوسطات الفروق لدرجات الاختبار القبلي والبعدي في تنمية مهارات ما وراء المعرفة لطلبة المجموعة التجريبية الذين درسوا المادة الدراسية على وفق البرنامج المحوسب (EWB)، والمجموعة الضابطة الذين درسوا المادة نفسها على وفق الطريقة الاعتيادية) وتحدد البحث الحالي بطلبة المرحلة الثالثة - قسم الفيزياء – كلية التربية – جامعة القادسية ، مادة مختبر الالكترونيات ) التجارب العملية (الفصل الدراسي الثاني – من العام الدراسي (2017- 2016)تم اعتماد التصميم التجريبي ذا الضبط الجزئي للمجموعتين المتكافئتين ) مجموعة تجريبية ، ومجموعة ضابطة ( ذوات الاختبار القبلي والبعدي ، تم اختيار شعبة ) ب ( اختيارا عشوائيا من بين الشعبتين الدراسيتين) أ ، ب( فتم تقسيمها إلى ثلاث مجاميع C , B , A)) بواقع (18، 16، 16) على التوالي وبالطريقة العشوائية تم اختيار المجموعة(B ) لتمثل المجموعة التجريبية والتي درست المادة العلمية على وفق البرنامج الإلكتروني المحوسب (EWB)، ومجموعة (C) لتمثل المجموعة الضابطة التي درست المادة الدراسية نفسها على وفق الطريقة الاعتيادية ، كوفئت مجموعات البحث بالمتغيرات التالية: ( والعمر الزمني ، والذكاء ، التحصيل السابق، ومقياس مهارات ما وراء المعرفة) ، قام الباحثان ببناء أداة البحث اللازمة والمتمثلة ببناء مقياس مهارات ما وراء المعرفة وهو تألف بصورته النهائية من (٥٢) فقرة موزعة على ست مجالات هي (المعرفة التقريرية. والمعرفة الإجرائية والمعرفة الشرطية والتخطيط والمراقبة والتحكم والتقويم)، واستخرج الباحثان الخصائص السايكومترية للاختبار، طبقت التجربة في الفصل الدراسي الثاني من العام الدراسي (٢٠١٦ -٢٠١٧) واستمرت طوال الفصل الدراسي الثاني على مدى (١٣) أسبوع بواقع ثلاث ساعات أسبوعيا لكل مجموعة بعد الانتهاء من تطبيق التجربة، الخاتمة توصلت الدراسة إلى (النتائج):- (فاعلية البرنامج الإلكتروني (EWB) قائم على النمذجة والمحاكاة في تنمية مهارات ما وراء المعرفة لطلبة المرحلة الثالثة - قسم الفيزياء - في مادة مختبر الإلكترونيك بالمقارنة مع الطريقة الاعتيادية، وفي ضوء تلك النتائج قدم الباحثان عدد من التوصيات وعدد من والمقترحات).
The present research aims to identify the impact of an electronic program based on modeling and simulation in the development of the skills of the students of the Department of Physics - Faculty of Education - University of Qadisiyah To achieve the research objective, the following null hypothesis was formulated: There are no statistically significant differences at the level of (0.05) between the average differences between the pre-test and the post-test levels in the development of the meta skills of the experimental group students who studied the subject according to the EWB program and the control group who studied the same material on According to the usual method). The current research included the third stage students- Physics Department - Faculty of Education - University of Qadisiyah, the module of the electronics laboratory (practical experiments), 2nd semester - the academic year (2016-2017). The experimental design with partial adjustment of the two groups (experimental group, and control group) with pre-test and post-test was chosen randomly from the two divisions A and B and divided into three groups (C, B, A) (16, 18, 16, 16) respectively. In a random way, group B was chosen to represent the experimental group, which studied the scientific subject according to the Electronic Program (EWB) and the C group to represent the control group that studied the same subject according to the method Typically, the research groups are equivalent to the following variables: (Time, intelligence, past achievement, and the Metacognitive). The researchers built the necessary research tools, namely the building of the skills level of knowledge beyond the knowledge of the final form of (52) paragraphs distributed in six areas (knowledge of the report and knowledge of procedural and knowledge of policing, planning, control, control and calendar) and the researchers extracted the characteristics of cytometric testing of the experiment In the second semester of the academic year (2016 - 2017) and continued throughout the second semester over a period of (13) weeks, three hours per week for each group after the completion of the experiment. The study concluded the effectiveness of EWB program based on modeling and simulation in the development of the skills of the students of the third stage - physics department - in the electronic laboratory material compared with the normal method. In light of these conclusions, the researchers presented recommendations and suggestions
Keywords: البرنامج المحوسب -- النمذجة -- المحاكاة -- مهارات ما وراء المعرفة -- طلبة الجامعات